Hispanics in the Mormon Zion, 1912-1999 - Iber, Jorge, 1961- (Elma Dill Russell Spencer series in the West and Southwest ;, 2000)
"Iber considers why many in the Utah Hispanic comunidad are leaving Catholicism for the Church of Jesus Christ of Latter-day Saints (LDS). He examines how conversion affects the Spanish-speaking population and how these Hispanic believers are affecting the Mormon Church." "Iber also concentrates on the geographic separation of Hispanics in Utah from their Mexican, Latin American, New Mexican, and Coloradoan roots. He examines patterns of Hispanic assimilation and acculturation in a setting which is vastly different from other Western and Southwestern states." "Hispanics in the Mormon Zion, 1912-1999 is an important source for scholars in ethnic studies, American studies, religion, and Western history. Drawing on both oral and written histories collected by the University of Utah and many notable organizations including the American G.I. Forum, SOCIO, Centro de la Familia, the Salt Lake Catholic Diocese, and the LDS Church, Iber has compiled an interesting and informative study of the experience of Hispanics in Utah."--Jacket